Effect of different types of mulches on growth and yield of turmeric - Hoque, M M; Begum, S; Rahman, M S; Alam, A B M S; Zhuma, M A A; Manik, M M H (Bangladesh Journal of Nuclear Agriculture, 2025)
The experiment was conducted at the Bangladesh Institute of Nuclear Agriculture (BINA) sub-station Khagrachari during 2020-2021 to compare the effect of different mulches on the growth and yield of Binahalud-1. Experiment was conducted with different organic mulches vizs., bamboo leaf, paddy straw, water hyacinths, and silver color plastic. A treatment without mulching was also kept as a control. The experiment was laid out in a randomized block design with three replications. The results indicated that the plants mulched with bamboo leaves recorded maximum average plant height of 150 cm, number of leaves 71.333, number of tillers 11, leaf length and leaf width 80 cm, 16.66 cm, leaf weight 29.33 gm, petiole length 40 cm and petiole weight 17.33 gm as compared to other mulches. In case of the yield of turmeric, the bamboo leaf mulch gave maximum fresh rhizome yield of 33.2 t ha-1 . From this study it is revealed that among the treatments bamboo leaf is the best mulch material for turmeric production. Bangladesh J. Nuclear Agric, 38(2): 161-167, 2024